2010
DOI: 10.1042/cs20100241
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity, toxicology, pharmacokinetics and pharmacodynamics of growth hormone ligand–receptor fusions

Abstract: A fundamental concern for all new biological therapeutics is the possibility of inducing an immune response. We have recently demonstrated that an LR-fusion (ligand-receptor fusion) of growth hormone generates a potent long-acting agonist; however, the immunogenicity and toxicity of these molecules have not been tested. To address these issues, we have designed molecules with low potential as immunogens and undertaken immunogenicity and toxicology studies in Macaca fascicularis and pharmacokinetic and pharmaco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
(54 reference statements)
0
9
0
Order By: Relevance
“…Most PDLCs in periodontal lesion tissues, however, require the inflammatory-free microenvironments and biological activity for periodontal wound healing. The addition of exogenous growth factors has been shown to improve osteogenic differentiation of PDLCs [11], but large-scale utilization of growth factors is clinically impracticable due to safety concern [12]. Therefore, it is of significance to develop new approaches to improve the osteogenic potential of PDLCs.…”
Section: Introductionmentioning
confidence: 99%
“…Most PDLCs in periodontal lesion tissues, however, require the inflammatory-free microenvironments and biological activity for periodontal wound healing. The addition of exogenous growth factors has been shown to improve osteogenic differentiation of PDLCs [11], but large-scale utilization of growth factors is clinically impracticable due to safety concern [12]. Therefore, it is of significance to develop new approaches to improve the osteogenic potential of PDLCs.…”
Section: Introductionmentioning
confidence: 99%
“…It appears that adding certain proteins to the C-terminus of GH such as albumen, CTP, Fc fragment and XTEN can delay clearance 17 . We previously undertook pharmacokinetic studies with our GHR agonist in non-human primates and based on allosteric modelling calculated that the fusion would only need to be administered once every 3 weeks 15 . Accepting that a GHR antagonist is required at higher concentration we can anticipate that GHA3 may only need to be administered once a week.…”
Section: Discussionmentioning
confidence: 99%
“…The pharmacokinetic characteristics suggested this fusion molecule could provide GH agonist therapy requiring injection every 21–28 days compared to daily GH administration. Thus, this technology clearly demonstrated that fusion to GH binding protein is an effective technology to delay clearance 15 . We have now tested whether a fusion of the GHR antagonist molecule to the GH binding protein could generate a long acting GHR antagonist and the hypothesis that introducing an amino acid change in the GH binding domain (W104A) would increase bioactivity.…”
mentioning
confidence: 84%
“…Furthermore, a single injection of GH-GHBP has bioactivity similar to a daily equimolar dose of GH when given to rats over a 10-day period 13 . The GH-GHBP fusion mimics the natural partnership of the separate GH and GHBP molecules and so was theorized to have low immunogenicity; in vivo immunogenicity studies confirmed this and also showed that GH-GHBP had low toxicity 14 . These initial results suggest that the GH-GHBP fusion could be administered weekly, or even less frequently, instead of the daily injections required for GH.…”
Section: Featuresmentioning
confidence: 98%